Blood Sisters - Keating, Barbara and Keating, Stephanie (Vintage Books, 2006)
During their childhood years in the Kenya Highlands of the 1950s, three girls from vastly different backgrounds become blood sisters, promising that nothing will ever destroy the bond between them. But as they grow up love rivalries, broken promises and the tensions and violence of a newly independent Kenya threaten to tear their childhood dreams apart.
Keywords: Fiction; Sagas